EFL Teacher’s Perspectives on Integrating AI into Reading Comprehension Teaching in Papua - Heni Purwati; Rahmawansyah Rahmawansyah; Anggit Prasetio Nugroho (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This study explores EFL teachers’ perspectives on integrating Artificial Intelligence (AI) technologies into reading comprehension instruction in Papua, Indonesia. This study employed a quantitative descriptive survey, conducted with 17 teachers from elementary, junior high, and senior high schools. Data were collected through an online questionnaire and analyzed using descriptive statistics. Findings showed that teachers were generally familiar with AI and express confidence in its use, particularly with widely accessible tools such as ChatGPT and Grammarly. Teachers viewed AI as beneficial for enhancing comprehension and providing personalized support, yet remained cautious about its potential to motivate students. Challenges on AI usage included lack of training, limited infrastructure, and ethical concerns such as plagiarism and student over-reliance. Teachers emphasized the importance of having access to AI-based tools, opportunities for peer collaboration, and focused professional development in order to overcome these challenges. The study indicates that although integrating AI has the potential to enhance reading comprehension, adoption of this technology is still at a transitional stage. Clear ethical standards, fair resource distribution, and teacher-centered training will all be necessary for successful implementation.